PENGEMBANGAN SINKRONISASI MULTIPLE BOOKING AND PAYMENT SITE DALAM SATU DASHBOARD - I Gede Totok Suryawan; Ary Wira Andika (LPPM Universitas Dhyana Pura, 2018)
ABSTRACTThis paper discusses the development of tour and activities product management, booking engine and payment facilities that are integrated with the payment gateway. This is done to solve problems experienced by tour and activities business owners related to product management facilities, booking engines, and payments on their website. Most of the tour websites and activities are not equipped with product management, booking engines, and payments, so they require special skills in managing the website, also allowing loss due to cancellation of transactions carried out by tourists. In this study an engine for product management, booking engine, and payment has been developed that is integrated with the payment gateway. The method used in developing this system uses Scrum model ranging from determining product backlogs, sprints, scrum meetings, to demo to clients. The results of the study show that the system developed can facilitate tour and activity business owners in managing tour products and activities, and facilitate tourists in ordering and paying for their products.Keywords: Booking Engine, Payment Gateway, Tour and Activities, Scrum Model.ABSTRAKPaper ini membahas tentang pengembangan manajemen produk tour dan activities, booking engine dan fasilitas pembayaran yang terintegrasi dengan payment gateway. Ini dilakukan untuk menyelesaikan masalah yang dialami oleh pemilik usaha tour dan activities terkait dengan fasilitas manajemen produk, booking engine, dan pembayaran di website mereka. Sebagian besar website tour dan activities sekarang tidak dilengkapi dengan manajemen produk, booking engine, dan pembayaran, sehingga memerlukan keterampilan khusus dalam mengelola websitenya, juga memugkinkan timbul kerugian akibat pembatalan transaksi yang dilakukan oleh wisatawan. Pada penelitian ini telah dikembangkan sebuah engine untuk manajemen produk, booking engine, dan pembayaran yang terintegrasi dengan payment gateway. Metode yang digunakan dalam pengembangan sistem ini menggunakan Scrum model mulai dari menentukan product backlog, sprint, scrum meeting, hingga demo ke client. Hasil penelitian menunjukkan bahwa sistem yang dikembangkan dapat mempermudah pemilik usaha tour dan activities dalam mengelola produk tour dan activitiesnya, serta memudahkan wisatawan dalam melakukan pemesanan dan pembayaran produknya.Kata Kunci : Booking Engine, Payment Gateway, Tour dan Activities, Scrum Mod